2021
DOI: 10.5194/hess-25-1333-2021
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic regimes drive nitrate export behavior in human-impacted watersheds

Abstract: Abstract. Agricultural watersheds are significant contributors to downstream nutrient excess issues. The timing and magnitude of nutrient mobilization in these watersheds are driven by a combination of anthropogenic, hydrologic, and biogeochemical factors that operate across a range of spatial and temporal scales. However, how, when, and where these complex factors drive nutrient mobilization has previously been difficult to capture with low-frequency or spatially limited data sets. To address this knowledge g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 61 publications
(79 reference statements)
1
18
0
Order By: Relevance
“…Across both long and short timescales, a consistent finding is that, within a particular catchment, the C-Q relationship (and thus export behaviour) is dependent on whether streamflow is dominated by baseflow or quickflow, i.e. the baseflow contribution to total flow (Gorski and Zimmer, 2021;Knapp et al, 2020;Minaudo et al, 2019). These studies also identified baseflow contribution as a key driver of the variation in C-Q relationships across catchments (Musolff et al, 2015;Moatar et al, 2017).…”
Section: Introductionmentioning
confidence: 78%
“…Across both long and short timescales, a consistent finding is that, within a particular catchment, the C-Q relationship (and thus export behaviour) is dependent on whether streamflow is dominated by baseflow or quickflow, i.e. the baseflow contribution to total flow (Gorski and Zimmer, 2021;Knapp et al, 2020;Minaudo et al, 2019). These studies also identified baseflow contribution as a key driver of the variation in C-Q relationships across catchments (Musolff et al, 2015;Moatar et al, 2017).…”
Section: Introductionmentioning
confidence: 78%
“…Whereas, the transport of SRP is confined to shallower soil layers that are activated only in wetter years. 4; Gorski and Zimmer, 2021). The lack of difference in SRP C-Q slopes between the 2 years, both annually and during March-July, suggests that transport of SRP is more strongly influenced by precipitation and stream discharge than C-Q dynamics.…”
Section: Connections Between Tile Drainage Stream Discharge and Nutrient Transportmentioning
confidence: 95%
“…However, as the contributing area shrinks following precipitation events, near-stream areas with greater denitrification rates and lower nitrate concentrations contribute relatively more to stream discharge compared to upland areas with greater nitrate concentrations (Marinos et al, 2020), resulting in contributing areas with more heterogeneous nitrate concentrations and a more chemodynamic nitrate C-Q behavior. For examples Marinos et al (2020) and Gorski and Zimmer (2021) found chemodynamic nitrate C-Q behavior to be dominant at low flows, while chemostatic nitrate C-Q behavior was more common during high flow events. These observations are consistent with our results showing more chemodynamic nitrate C-Q behavior in 2018, compared to the chemostatic response observed in 2019.…”
Section: Connections Between Tile Drainage Stream Discharge and Nutrient Transportmentioning
confidence: 96%
See 2 more Smart Citations